Structural tuning of zinc–porphyrin frameworks via auxiliary nitrogen-containing ligands towards selective adsorption of cationic dyes. Issue 46 (17th May 2019) - Wang, Xiao-Ning; Li, Jiang-Li; Zhao, Yu-Meng; Pang, Jiandong; Li, Bao; Zhang, Tian-Le; Zhou, Hong-Cai
Abstract : Three novel zinc–porphyrin MOFs have been synthesized by using versatile N-containing ligands. The open Watson–Crick pair in the interior surface in one Zn-MOF has been presented, which could endow the related MOF with excellent selective adsorption of dye molecules. Abstract : Three metal–organic frameworks have been synthesized by using N-containing ligands and meso -tetra(4-carboxyphenyl)porphyrin, which all exhibit distinct selective adsorption capacities toward various organic dyes, illustrating the most important influence of the structural tuning.